Prince Charoon and others South East Asia - Dalby, Andrew 1947- (Haus histories, 2011)
Southeast Asia needs to be dealt with as a whole, because, although the one national delegation from the region (Siam) took a minor part, nationalist movements in several Southeast Asian countries reached an early climax significant though inconclusive in the years 1919-1920. The planned Peace Conference, Wilson's Fourteen Points, and the victory of Communism in Russia, all contributed to this activity, and in spite of national differences it needs to be seen as a whole. The focus of the book will be on developments around 1919; thus it will bring out for the first time the unexpected significance for South-east Asia of the 1919 milestone. It will also have a biographical bias taking a special interest in the personalities of major figures in this important period, in order to show the influences and the patterns of thought that underlie their activities at the time of the Peace Conference. Following a brief introduction making the link between world events in 1919 and South-east Asia, the book sets the scene in the region.